Employing social media based willingness to communicate (wtc) module in english speaking skill instruction - Anna Lynn Abu Bakar; Wardatul Akmam Din; Suyansah Swanto; Darmesah Gabda (Global Academic Excellence, 2023)
Having a sense of willingness to communicate (WTC) in the 2nd language (L2) is one of the important factors in improving ESL students’ speaking skills. WTC model is used as an indicator for successful English learning outcome. This study looks at the impact of the employment of WTC on ESL students’ speaking skill by integrating the employment of social media applications in a digital English-Speaking classroom setting. This study employs multi-methods approach using purposive sampling technique involving questionnaire responses of 421 students to identify successful WTC strategies to be integrated in the module; a pre- and post-test to look at impact of the module and focus group interview of 17 pre-university students to investigate their opinion on the module. The findings of the study revealed that students’ WTC were very much influenced by the use of social media applications in a digital classroom. The interview data also showed that students were more engaged and had higher WTC when social media applications were used. These findings are seen as valuable input especially to English language instructors in integrating social media applications in their teaching and learning in order to engage and increase their WTC in English in the classroom.